Achieving competitive advantage by employing value stream Technology - Nada Mohamed Fadel; Abdel Reda Latif Jassim (Journal of Madenat Alelem University College, 2022)
The adoption of industrial economic units in Iraq has traditional cost systems that cause many problems in calculating the costs of its products (goods and services), such as high costs and low quality of those products, because these systems do not provide the appropriate cost information that these units need in the correct exercise of their main tasks such as planning, control and decision-making, As well as its inability to keep pace with developments in the market, which makes the possibility of its persistence very weak, and consequently losing its competitive position and market share and its exit from the market. Therefore, those units must find modern techniques and systems that enable them to measure their cost in an appropriate and accurate manner and add value to their products. By providing low cost and high quality products. The research was based on a basic hypothesis that (the employment of the value stream technology contributes to achieving competitive advantage), and the most prominent findings of the research are that the employment of the value stream contributes to enhancing the value of the industrial economic unit by reducing costs and improving value, by excluding Costs that do not add value and are unnecessary while maintaining the desired level of quality and maximizing perceived value to the customer.